Transportation scenario of Black Bengal goats in Gabtoli and Sirajganj markets of Bangladesh (Journal of Advanced Veterinary and Animal Research, 2016)
Objectives: This study was designed to reveal out the present transportation scenario of Black Bengal goats to and from some selected markets in Bangladesh.  Materials and methods: A questionnaire survey to know the behavioral parameters and  management  provisions  provided  by  the  farmers  was  designed  to  collect necessary information from Sirajganj and Gabtoli markets. The survey was conducted by  direct  interview  with  the  stakeholders  who  were  directly  involved  with  the transportation of Black Bengal goats from Sirajganj to Dhaka city.   Results: The present study showed that 58% adult respondents were involved in goat transportation  program,  among  them  95%  were  male.  Most  of  the  farmers  in  the markets  lacked  institutional  education  (24%)  or  just  completed  primary  education (41%). Only 27% of the respondents had earlier experience in transporting animals. Transport durations were 6 h (10%). The goats were usually  transported  on  foot  or  by  using  vehicles.  All  the  respondents  were  known about  planning  of  animal  transportation.  About  2,  5,  7  and  5%  of  animals  were suffering from head swinging, stretching, stamping of feet and paralyzed condition during transportation,  respectively.  During  transportation,  the  animals  exhibited idleness  (25%),  panting  (17%),  foaming  (14%),  vocalization  (13%)  and  moving forward  (12%).  Most  of  the  farmers  provided  feed  (41%),  rest  (33%)  and  shelter (24%) during the transportation of the goats. Only 5% farmers hired trained drivers for transportation purpose. About 27% animals were untied and 7% animals ramped during  transportation.  Besides,  there  were  high  percentage  of  pressure  to  animals (23%),  hitting  or  kicking  animals  (19%)  and  abuse  to  animals  (15%)  during transportation. Conclusion:  From  this  study  it  is  concluded  that  Black  Bengal  goats  became physically unfit during long time transportation although majority of the farmers took proper management practices. Therefore, changes in behavioral responses might be alleviated through creating awareness to animal raiser as well transporter.http://dx.doi.org/10.5455/javar.2016.c129